Significant Association Between Increased Abundance of Selected Bacterial Lipopolysaccharides and Norovirus Diarrhea Among South African Infants - Lerato P. Kgosana; Mapaseka L. Seheri; Cliff A. Magwira (Viruses)
Bacterial lipopolysaccharides (LPS) have been shown to promote enteric viral infections. This study assessed whether possessing elevated levels of LPS was associated with norovirus infection. Fecal samples from diarrheic norovirus-positive (DNP) (n = 26), non-diarrheal norovirus-negative (NDNN) (n = 26), asymptomatic norovirus-positive (ANP) (n = 15), and diarrheic norovirus-negative (DNN) (n =15) infants were assayed for selected bacterial LPS by quantitative PCR. The mean levels of selected LPS gene targets were significantly high in DNP infants (6.17 ± 2.14 CFU/g) versus NDNN infants (4.13 ± 2.25 CFU/g), p = 0.003. So too was the abundance between DNP and DNN infants (p = 0.0023). The levels of selected LPS gene targets were high regardless of whether the infection was symptomatic or asymptomatic, p = 0.3808. The average expression of genes coding for selected LPS and their signalling molecule, Toll-like receptor 4 (TLR4), increased 7- and 2.5-fold, respectively, in DNP versus NDNN children. Infants possessing elevated levels of selected LPS-rich bacteria were 1.51 times more likely to develop norovirus diarrhea (95% CI: 1.14–2.01, p = 0.004). In conclusion, norovirus infection was associated with abundance of selected bacterial LPS, suggesting a possible role of bacterial LPS in norovirus infection.